DFT Method, Molecular Orbital’s, and Electronic Spectra Study for Characterization the Biological Activity of New Ebselen [2-phenyl-1, 2- Benzisoselenazol-3(2H)-one] Derivatives - Ahmed Abdul Sattar Ali (Journal of Global Pharma Technology, 2016)
Glutathione peroxidase (GPx) is one of the most potent antioxidant enzymes that is based on the selenium metal ion in the active site and plays an important role in reducing hydrogen peroxide and lipids. As low levels of GPx lead to an increase in hydrogen peroxide levels and thus cause direct damage to living tissue and many diseases infection. The number of selenium-containing compounds has been developed for their ability to treat or minimize peroxides. Ebselen “2-phenyl-1, 2- benzisoselenazol-3(2H)-one” is one of the most promising compounds as an antioxidant and have been shown to mimic the glutathione peroxidase activity in vitro. In this paper, seven different chemical derivatives of ebselen (a compound scientifically proven as an antioxidant) were designed by replacing or adding chemical groups and studying the effect of these changes on the behavior and effectiveness of the compound by studying the electron density of the central atom (selenium), HOMO, and LUMO. The stable geometrical shape of the compounds was also determined by calculating frequencies, bond energies and ion extraction for derivative compounds. On the other hand, the polarity of these derivatives and their solubility were calculated as well as the calculation of the Mulliken charge and electronic spectra measurements “infra Red (IR), UV-visible”. Some of the compounds were characterized by having a better biologic effect than Ebselen while some of the derivatives were reversed.Keywords: Glutathione peroxidase (GPx), Ebselen, HOMO, LUMO, Density Functional Theory (DFT), Becke3-Lee-Yang-Parr (B3LYP).